The Concept of Market Segmentation: a Framework for Effective Marketing Strategies - Abdusaitovich, Rakhimov Hasan (Journal of Innovation in Education and Social Research, 2024)
This research paper delves into the concept of market segmentation, a fundamental tool in modern marketing strategies. It examines the rationale behind market segmentation, exploring its benefits and challenges. The paper outlines various segmentation bases and strategies, emphasizing their relevance to different marketing objectives. Furthermore, it discusses the process of market segmentation, from identifying target audiences to tailoring marketing campaigns for optimal impact.